Assessment in Islamic Higher Education - Erwin Hafid (Institut Agama Islam Negeri (IAIN) Manado, 2016)
Assessment is an important part of learning and teaching in educational institutions, including Islamic institutions. Therefore, assessment should guarantee that it can be used to improve learning and teaching. This article concludes that formative assessment is more useful and beneficial to Islamic higher education, because it will encourage more to learning than summative assessment will. However, this kind of assessment seems more difficult to be valid and reliable in grading. Creating rubric may become a solution to avoid such a problem.